Depression and religious practices in inmates of a prison in Cusco-Peru - Yunguri Arias, Viki (2021)
The objective of the study was to determine the relationship between depression and religious practices in inmates of a Penitentiary Establishment in Cusco-Peru. The Beck Depression Inventory (BDI - II) (Beck et al., 2006) and the Religious Practices Scale adapted to the prison context (Hamann, 2003) were applied to a sample of 380 inmates for different crimes. The results show that there is no relationship between depression and religious practices. However, a relationship was found with the indicator “I behave as God expects me to do it”. 71% of the sample has some level of depression: 24.7% of inmates have mild depression, 22.45% moderate depression and 24.2% severe depression. It was also obtained that 62.8% of inmates have religious practices. The most frequent are pray to God to ask for help (61.1%), thank God (56.1%), transmit their faith to people close to them (36.6%), read the Bible (25.5%) and attend religious celebrations held inside the prison (25%).